Indirect Estimation of the Development of Capital Productivity in the Regions: The Case of Poland - Zdražil, Pavel; Kraftová, Ivana (My University, 2021)
This study introduces anew (adopted) method of indirect estimation of the development of the productivity structure in the regions, which at the same time allows estimation of the contribution resulting from changes within the capital factor. Its theoretical background is built on the principles of growth accounting. Within this framework the study employs an arguable assumption of analogy in development of multifactor productivity of industry between the national and regional level. The literature review and empirical results shows, however, that such an assumption may be correct in some cases. Therefore, the article enhances the existing productivity analysis capabilities at the regional level. Within the aim, this study verifies the potential of applicability of proposed method on the regions of Poland. It uses the measure of symmetric mean absolute percentage error (SMAPE) to evaluate the accuracy of method proposed against actual values and the results of two other frequently used methods for disaggregation of capital among the regions in acountry. The results indicate that the new method should be more accurate than the methods of regional decomposition of capital-based on value added, and flows investment accumulation. In fact, it seems to be quite correct especially in the industries of wholesale & retail trade, transport & storage, real estates, health & social work, and manufacturing. On the other hand, it is likely incorrect in the industries of information & communication activities, finance & insurance, and administrative & support activities. In general, the method seems to be more accurate for larger industries and vice versa. Higher precision is also observed for industries where capital demand is clearly increasing. Similarly, the method is more accurate in industries where none of the regions are more specialized and vice versa.
Nepřímý odhad vývoje produktivity kapitálu v regionech: aplikace na příkladu regionů Polska
Keywords: capital; productivity structure; regional growth; growth accounting; regional decomposition; kapitál; struktura produktivity; regionální růst; růstové účetnictví; regionální dekompozice